Frida [videorecording (DVD)] - Taymor, Julie, 1952-; Hayek, Salma, 1966-; Molina, Alfred, 1953-; Golino, Valeria; Herrera, Hayden (Miramax Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2003)
The life of artist Frida Kahlo, from her humble upbringing to her worldwide fame and controversy that surrounded both her and her husband, Diego Rivera.